Comparison between transthoracic echocardiography and transoesophageal echocardiography in the diagnosis of acute aortic dissection from an emergency perspective. A systematic review and meta-analysis - Zaki, Hany A.; Albaroudi, Bilal; Shaban, Eman E.; Alkahlout, Baha Hamdi; Yigit, Yavuz; Elnabawy, Wael; Basharat, Kaleem; Almarri, Nood Dhafi; Azad, Aftab Mohammad (Frontiers in Cardiovascular Medicine, 2024)
Background Acute aortic dissection (AAD) is a life-threatening medical condition with high early fatality. Therefore, a prompt and precise diagnosis, which can be achieved through invasive and non-invasive techniques is vital. Echocardiography, unlike MRI and CT, is accessible in emergency units and bedside-compatible. The recommended echocardiographic techniques for AAD are transthoracic and transoesophageal echocardiography (TTE and TOE). Therefore, our review compares their diagnostic roles in AAD. Methods Studies relevant to our topic were attained through a database search and manual scrutiny of references lists of articles obtained from the electronic databases. The Quality Assessment of Diagnostic Accuracy Studies tool (QUADAS-2) has been used for quality assessment. All quantitative analyses were performed using either STATA 16 or Comprehensive Meta-Analyst software. Results The search strategy yielded 1,798 articles, of which only 11 were eligible for inclusion. Our subgroup analysis showed that conventional TTE had a sensitivity and specificity of 85.35% and 84.51% for the diagnosis of Stanford type A AAD and was 45.89% sensitive and 87.05% specific for the diagnosis of type B AAD. However, the subgroup analysis shows that contrast-enhancement of TTE results in a sensitivity and specificity of 93.30% and 97.60% for diagnosis of type A AAD, and 83.60% and 94.50% for diagnosis of type B AAD, respectively. On the other hand, conventional TOE was 93.64% sensitive and 95.50% specific for the diagnosis of type A AAD, 99.80% sensitive and 99.87% specific for the diagnosis of type B AAD. Moreover, our analyses show that TTE has pooled false negative and positive rates of 28.6% and 18.6%, while TOE has shown false negative and positive rates of 2.4% and 4.3%, respectively. Conclusion TOE is the more favorable diagnostic tool for AAD diagnosis than TTE. However, it cannot be used as a stand-alone diagnostic tool since misdiagnosis cases are being reported. Contrast-enhanced TTE can also diagnose AAD since it provides similar results to conventional TOE.